Maintaining Gaps in Teacher Diversity, Preparedness, Effectiveness, and Retention? A Program Theory Evaluation of Mathematics Teacher Training in the New York City Teaching Fellows. Issue 6 (September 2022) - Brantlinger, Andrew; Grant, Ashley A.; Miller, Julie; Viviani, William; Cooley, Laurel; Griffin, Matt
This study examines the extent to which the New York City Teaching Fellows (NYCTF) has delivered on its promise of improving mathematics teacher diversity, preparedness, effectiveness, and retention in hard-to-staff city schools. As a program theory evaluation study, it articulates the theory of action for selective alternative route programs and uses this to evaluate NYCTF's program for secondary mathematics. The analysis draws on longitudinal data from 620 secondary mathematics teachers who began NYCTF in the prior decade. While the results point to potential improvements, it provides evidence that selective programs like NYCTF serve to maintain important gaps in teacher quality that they were designed to address.